Short Version of V.A. Losenkov's Impulsivity Questionnaire: Development and Validation - Viktor P. Sheinov; Anton S. Dziavitsyn (Peoples' Friendship University of Russia (RUDN University), 2022)
Impulsivity is considered as a personality trait opposite to purposefulness and perseverance; accordingly, a high level of impulsivity is inherent in people with insufficient self-control in communication and activity. Impulsivity as a subject of research is of both theoretical and practical interest; however, methods for diagnosing it are poorly represented in the Russian-language psychological literature. The purpose of the research is to study the factor structure, reliability and validity of the short version of V.A. Losenkov's impulsivity questionnaire developed by the authors. The first part of the study involved 967 subjects (M = 21.2, SD = 7.7), including 652 women (M = 21.6, SD = 7.8) and 315 men (M = 20.6, SD = 7.4); in the second part, 233 respondents participated, including 126 women (M = 21.4, SD = 7.7) and 107 men (M = 20.8, SD = 7.3). The study was conducted using: (1) the full version of V.A. Losenkov' impulsivity questionnaire; (2) Barratt's impulsiveness questionnaire (adapted in Russian by S.N. Enikolopov and T.I. Medvedeva); (3) A.V. Zverkov and E.V. Eidman's volitional self-control questionnaire; (4) A. Assinger's aggressiveness questionnaire; and (5) questionnaires on assertiveness, smartphone addiction and social media addiction developed by the authors. The abridged version of V.A. Losenkov's impulsivity questionnaire (Imp-15) includes 15 tasks that make up a four-factor model of impulsivity obtained through exploratory and confirmatory factor analysis. Compared with the original version of the questionnaire, the abridged version has better psychometric properties. The abridged Imp-15 version satisfies the standard requirements for questionnaires in terms of their reliability, namely: internal consistency, high task distinguishability and retest reliability. The questionnaire also meets key validity criteria in terms of its design, content, "obviousness," actual and predictive credibility, constructability and convergence. Impulsivity diagnosed by the Imp-15 questionnaire positively correlates with the data of the Barratt Impulsivity Scale (BIS-11), with aggressiveness, smartphone addiction and social media addiction; however, it is negatively associated with self-control and assertiveness. The resulting four-factor model of impulsivity has good reliability indicators and is in full agreement with the obtained data. The authors present the data of psychometric testing and standardization of the abridged Imp-15 questionnaire; the appendix provides the original and abridged versions of the impulsivity questionnaire and the keys to the Imp-15 questionnaire.